Evidences of the charge fundamental asymmetry - LUTEPHY, Mohsen (Contributions to Geophysics and Geodesy, 2019)
There is an infinitesimal small non polarizable electric inertial charge in the individual atoms or in a number neutral matter included to equal number of the electrons and protons. We refer to the pure calculations verified by the experimental laboratorial results, also planetary phenomena and cosmic observations. This inertial electric charge is origin of a part of the measurable magnetic field in addition to self-consistent dynamo, together as complementary origins to generate very complex magnetism of the celestial bodies. Ultimately we refer to the null results of the test experiments for the spinning bodies magnetic field and we see that neither used bodies in the experiments have been number neutral (no equal number of the electrons and protons), nor the simple formula of the Patrick Blackett is accurate in detail. But we have extracted a new formula in agreement for all spinning bodies magnetic fields, in agreement with both terrestrial and cosmic bodies. We verify the effect of electric charge asymmetry in expanding universe and acceleration of the universe expansion and anisotropy of cosmic microwave background and singularity paradox and solar wind and acceleration of solar wind and corona high temperature puzzle as an equilibrium between the gravity and antigravity and mysterious heat generation of the Sun and planets interiors and missing neutrino and the comets plasma tail outward direction and pendulums mysterious precessions and some other mysteries phenomena too.